Gods of Participation: Participatory Sense-making and an Enactivist Reframing of the Religion and Morality Problem - Ciołkosz, Matylda (Journal for the Cognitive Science of Religion, 2024)
This paper is a theoretical discussion of how the relation between religion and morality – one of the main research areas in the cognitive and evolutionary sciences of religion (CESR) – may be rephrased in terms of 4E cognition. This aim is realized through redefining morality and religion in terms of participatory sense-making – a model of social cognition situated within the 4E framework. This paper explains the basic tenets of the 4E (embodied, embedded, extended, and enactive) approach to cognition. It clarifies how the notion of mental representations – pivotal for any theorizing within CESR – can be fitted within this model by adopting a radical enactive cognition view. It then proceeds to define participatory sense-making and demonstrate how morality as a system for regulating cooperative behavior fits this concept. Finally, it discusses the role of representations of gods’ moral concerns in reinforcing morality. It argues that focusing on the meaning-making potential of social interactions can elucidate where these representations come from and how they unfold.